The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1108/ara-06-2015-0064
|View full text |Cite
|
Sign up to set email alerts
|

Segment reporting in a developing economy: the Indian banking sector

Abstract: Purpose The purpose of this paper is to investigate the value relevance of segment information for both public and private sector banks in India. In doing so, this paper examines a rapidly developing economy and perhaps its most critical sector during this period of strong economic growth. Design/methodology/approach In this study uses the simplified Ohlson model, for a sample of 136 private sector and public sector banks for the period 2007-2010 in India. Findings The paper finds that public sector banks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 62 publications
4
11
0
Order By: Relevance
“…The findings reveal that segmental disclosure (including the number of segments and the segment-related accounting details) for both Jordanian and Qatari listed firms, is both value relevant and significantly associated with share prices. These findings support prior studies (Chen and Zhang, 2003;Hossain and Marks, 2005;Hossain, 2008;Hope et al, 2008;Birt and Shailer, 2011;Kajüter and Nienhaus, 2017;Birt et al, 2017) which investigated the association between segment data and share prices. Results for these two developing countries in the Middle East are thus similar to findings relating to other developed and emerging nations.…”
Section: Segmental Reporting and Its Value Relevancesupporting
confidence: 90%
See 3 more Smart Citations
“…The findings reveal that segmental disclosure (including the number of segments and the segment-related accounting details) for both Jordanian and Qatari listed firms, is both value relevant and significantly associated with share prices. These findings support prior studies (Chen and Zhang, 2003;Hossain and Marks, 2005;Hossain, 2008;Hope et al, 2008;Birt and Shailer, 2011;Kajüter and Nienhaus, 2017;Birt et al, 2017) which investigated the association between segment data and share prices. Results for these two developing countries in the Middle East are thus similar to findings relating to other developed and emerging nations.…”
Section: Segmental Reporting and Its Value Relevancesupporting
confidence: 90%
“…They found that the amount of segmental information declined under IFRS 8, but the disclosures provided were value relevant. Birt et al (2017) have also examined the value relevance of segmental reportingonly for Indian banksand found that the number of segments for which disaggregated information was supplied was value relevant and was associated with higher share prices. The current study extends the literature by investigating the value relevance of segmental reporting following the post-implementation review of IFRS 8 across sectors and countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e In 2001, the Institute of Chartered Accountants of India (ICAI) implemented the obligation for segment reporting in the standard AS 17 -Segment Reporting (Reddy and Satish, 2001). With the harmonisation to IFRS, Ind AS 108 -Operating Segments has been in effect since April 1st, 2011, which requires companies to report both product and service-related segments and geographical segments (Birt et al, 2017). f All elements of the remuneration structure of the individual members of the management board have to be disclosed under main categories such as salary, benefits, bonuses, stock options and pensions in the annual financial statements [Chakrabarti et al, (2012); Clause 49 IV E (ii), entered into force on February 21st, 2000].…”
Section: Tablementioning
confidence: 99%